Hot-air drying of purslane (Portulaca oleracea L.) - Doymaz, Ibrahim (SPRINGER, 2013)
Drying characteristics of purslane was experimentally studied in a cabinet dryer. The experimental drying data were fitted best to Modified Henderson and Pabis and Midilli et al. models apart from other models to predict the drying kinetics. The effective moisture diffusivity varied from 1.12 x 10(-9) to 3.60 x 10(-9) m(2)/s over the temperature range studied and activation energy was 53.65 kJ/mol.
Keywords: EFFECTIVE MOISTURE DIFFUSIVITY; LAYER; KINETICS; MICROWAVE; BEHAVIOR; Thermodynamics; Mechanics